Developing an Instrument of Life Balance Factors among Female Engineers who have Family: The Application of Modified Delphi Technique - Sakinah Subri, Ummu; Che Rus, Ridzwan; Mustapha, Ramlee; Hanapi, Zaliza (International Journal of Psychosocial Rehabilitation, 2019)
This study aims to obtain expert approval and consensus on Life Balance construct instrument among female engineers who have family. The purpose of this instrument is to identify the factors that assist women engineers to have a well-balanced life. The technique used in developing this Life Balance instrument is the Modified Delphi technique. This technique was used to obtain consensus among experts in developing the Life Balance items. The instrument development was performed by seven experts who have expertise, experience, and knowledge in career and engineering fields. The initial results (interviews with experts) identified four key factors in achieving Life Balance which were childcare, flexible career, leave, and social support. An example of how to obtain an interquartile range (IQR) value using the Modified Delphi technique that was carried out for a second time until the consensus was achieved was provided. IQR value is a value derived from questionnaires completed by experts to obtain consensus on construct items and the data were analysed using Microsoft Excel